2020
DOI: 10.1016/j.xcrm.2020.100019
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome and COVID-19: A Perfect Storm?

Abstract: People with Down syndrome show signs of chronic immune dysregulation, including a higher prevalence of autoimmune disorders, increased rates of hospitalization during respiratory viral infections, and higher mortality rates from pneumonia and sepsis. At the molecular and cellular levels, they show markers of chronic autoinflammation, including interferon hyperactivity, elevated levels of many inflammatory cytokines and chemokines, and changes in diverse immune cell types reminiscent of inflammatory conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 93 publications
5
143
0
6
Order By: Relevance
“…In a recent study, it was reported that 30.4% of children admitted for hospitalisation were obese [18] and that obesity is prevalent in DS [19] This currently presents a challenge in distinguishing the role of comorbidities in the development of COVID-19 in DS. Research studies suggest that children with trisomy 21 could be genetically vulnerable to severe infections by the SARS-CoV-2 virus [1].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, it was reported that 30.4% of children admitted for hospitalisation were obese [18] and that obesity is prevalent in DS [19] This currently presents a challenge in distinguishing the role of comorbidities in the development of COVID-19 in DS. Research studies suggest that children with trisomy 21 could be genetically vulnerable to severe infections by the SARS-CoV-2 virus [1].…”
Section: Resultsmentioning
confidence: 99%
“…Research studies have showed that T cell lineages of adults with DS show clear signs of differentiation and hyperactivation even in the absence of any obvious infections, a phenomenon which may be attributed to chronic IFN hyperactivity [4]. These data indicate that the IFN response, which is crucial for escalating antiviral responses besides driving and amplifying the cytokine storm, is vigorous in people with DS [1].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations